2014
DOI: 10.1111/trf.12653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seven hepatitis B virus (HBV) nucleic acid testing assays in selected samples with discrepant HBV marker results from United States blood donors

Abstract: Highly sensitive NATs require new confirmatory algorithms as presented optimally using different genomic regions or sequence generation. The introduction of immigration-related HBV genotypes may impact HBV epidemiology in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…Therefore implementing a highly sensitive assay for HBV DNA screening in Lebanese blood donors, should be considered to avoid any false negative results. Previous studies have shown that various NAT commercial assays differ in their sensitivity (36)(37)(38), this could be associated with various factors such Hepat Mon. 2017; 17 (7):e14250.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore implementing a highly sensitive assay for HBV DNA screening in Lebanese blood donors, should be considered to avoid any false negative results. Previous studies have shown that various NAT commercial assays differ in their sensitivity (36)(37)(38), this could be associated with various factors such Hepat Mon. 2017; 17 (7):e14250.…”
Section: Discussionmentioning
confidence: 99%
“…However, HBV transfusion-transmission cannot be completely excluded since the pooling procedure reduces the assay's analytical sensitivity [9], and in fact a recent report indicated that the likelihood of detecting OBI donations by NAT increased when the size of the pool was decreased from 50 to 20 donations or when the test sensitivity was increased by a small margin [9][10][11]. As recently pointed out [5], studies on the safety of the current screening policies would require the testing of matched recipient specimens collected before and after transfusion.…”
Section: Introductionmentioning
confidence: 97%
“…Many countries have chosen to reduce the number of samples/pool by using mini pool (MP) testing, thus increasing the analytical sensitivity [66]. The detection of OBI donations by NAT is improved when the MP is reduced from 50 to 20 samples [33].…”
Section: Detection Of Occult Hepatitis B Infections In Blood Donorsmentioning
confidence: 99%